New media utilization among rural and urban youth in marginalized communities in Malaysia - Hassan, Shahizan; Shiratuddin, Norshuhada; Mohd Sani, Mohd Azizuddin; Ahmad, Mohd Khairie; Abd Rahman, Zainatul Shuhaida; Ahmad, Noor Sulastry Yurni; Aboo Talib @ Khalid, Kartini (Medwell Journal, 2016)
Studies have shown that marginalization has in impact on the level of youth participation and engagement in social, political and economic processes.This study presents a study that attempts to determine the way in which youth in marginalized communities utilize new media to participate in the decision making process.It also aims to identify issues commonly raised by the youth and to ascertain whether there are any differences in the issues raised by the rural and urban youth in the marginalized communities. Data gathering for this study includes focus group discussions involving 51 participants from five different states in Malaysia, development of new media portal for youth (i.e., youth 4 Malaysia) and five intervention/training programmers involving 393 rural and urban youth of marginalized communities in Malaysia (the northern, central, southern, eastern and Sabah and Sarawak).The findings show that the participating youth are more interested to voice out issues related to social aspects via new media platform, particularly issues related to living quality. Other important issues are freedom of speech under political category and rising cost of living under economy category.However, there are some differences in terms of the issues raised by the rural and urban participants.The urban youth are very worried about the rising crime rate whereas the rural youth are more interested in the rising cost of living issue and political stability.This study highlights the need for the government and relevant authorities to take into account various issues raised by rural and urban youth to ensure that their voices are heard and have an impact on the nation building.